Experiment on instantaneous value voltage control of a single-phase AC chopper - Polmai, S.; Sugprajun, E. (My University, 2007)
This paper reports experiment on the previously proposed instantaneous value voltage control of a single-phase ac chopper. The proposed control method is based on a modified carrier SPWM and instantaneous value voltage and current feedback control system. The validation of the proposed method is confirmed by experimental results. © 2007 IEEE.
Keywords: AC chopper; Automatic voltage regulation; Instantaneous value voltage control; Pulse-width modulation